"Contraband" Practice: Doing Environmental Justice with Water - Karen Bauer, Merle Geode, Simi Kang, Chika Kondo 近藤千嘉, David Naguib Pellow, 심제현 Jae Hyun Shim, and 신 선 영 辛善英 Sun Yung Shin (Open Rivers, 2019)

(untitled)
When I asked the following six artists, theorists, community advocates, organizers, and members to contribute to this issue, it was primarily to share a reading or practice related to water and environmental justice (EJ) in our Primary Sources column. In soliciting these citations, I also asked them to answer a series of questions (which you will find below)...